UNDERSTANDING REGIONAL INTEGRATION VARIATION AND THE ADOPTION OF NEW TECHNOLOGY: EU AND ASEAN LEGAL FRAMEWORK ON ELECTROMOBILITY IN COMPARATIVE PERSPECTIVES - Asrul Ibrahim NUR (Challenges of the Knowledge Society)
Climate change has a significant impact on multiple aspects of human life. The transportation sector, dominated by conventional vehicles, is one of the sources of carbon dioxide emissions that lead to climate change. Therefore, electric vehicle (EV) innovation is one of the prospective possible solutions. Multiple international organisations have adopted legal frameworks to encourage their member states to promote EV deployment within the energy transition framework and climate change adaptation. EU and ASEAN are two regional organisations that have adopted legal frameworks on electromobility. Furthermore, this study will discuss the variation and comparative influence of EU and ASEAN regional integration on adopting new technologies, namely EVs, in the context of climate change adaptation. The research method adopted in this study is comparative law by comparing two different legal systems with the same implementation period and circumstances. Moreover, this study aims to understand the effect of diverse regional integration on electromobility through adopting various legal instruments by regional organisations. A comparative study between the EU and ASEAN is still relevant due to the strengthening relationship between both organisations. Furthermore, in climate change, the EU has also been recognised as a global actor influencing many climate policy developments worldwide. Therefore, comparing the EU and ASEAN as regional organisations with their respective maturity and characteristics will provide a new perspective to analyse the development of electromobility. In addition, this study will also provide new research opportunities, particularly comparative law related to climate policy adopted by regional organisations.